Gender-related issues in a Taiwanese university medical science laboratory setting: a qualitative analysis - Tseng, Chun-Yi; Chang, Shu-Ching (Frontiers in Psychology, 2023)
This paper provides a glimpse into gender issues in a university-based medical science laboratory setting in northern Taiwan. In this study, gender issues with respect to perceptions regarding gender, the degree of gender neutrality in the work environment, and the influence of gender on researchers’ academic careers were analyzed. Methods: From July to August 2021, semistructured interviews to understand the perspectives of five faculty members at Chang Gung University School of Medicine regarding gender issues were conducted. The data were transcribed verbatim and analyzed thematically. Subsequently, coding was performed using ATLAS.ti Web (Version 4.0.10). Results and discussion: It was found that gender is not perceived to correlate with performance in the medical sciences. Although the medical science laboratories in the study institution are mostly gender-neutral, instances of discrimination might have been concealed elsewhere because of underreporting. Nevertheless, medical science research culture in Chang Gung University appears to promote respect and equality owing to increased general awareness regarding such issues as well as robust policies that protect women’s rights and promote gender equality. Marriage, motherhood, and family obligations remain key challenges to the academic career of female scientists in the institution. To achieve more equitable representation of male and female scientists as well as to prevent female scientists from leaving medical science laboratories in Taiwan, institutional and national policies that provide tailored support for female scientists intending to start families must continue to be implemented.